Maxillofacial fractures in patients treated at the Princess Marina Hospital, Gaborone - Juan Carlos Quintana Díaz; Carlos Alberto Botella Suarez; Evis Johnson Montero; Raquel Rojas Bruzón (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2022)
Background: Fractures of the maxillofacial complex constitute about half of all fractures, and in a large number of patients they are associated with other fractures and injuries. The etiology is varied, and requires fast, accurate, and timely diagnosis and treatment. The study of this entity is relevant to know its characteristics as part of emergency care; as well as its clinical and social implications. Objective: to describe the behavior of maxillofacial fractures in patients treated at the Maxillofacial Surgery service of Princess Marina Hospital, Gaborone, Botswana. Methods: a descriptive and retrospective study was carried out in the Maxillofacial Surgery service of the Princess Marina Hospital, in Gaborone, Botswana, from June 2018 to June 2020. All patients (N = 423) with diagnosis were included of maxillofacial trauma, and consequently, of some type of fracture of this part of the body. Absolute and relative frequency tables were used to show the information. Results: 423 patients with maxillofacial fractures were attended, among which the male sex predominated. The age group most affected was 26-35 years old; interpersonal violence, the most frequent cause; and skull injuries and fractures, the most common associated injuries. Conclusion: Results were similar to other published studies. Interpersonal violence exceeded traffic accidents as the most common cause of maxillofacial fractures.